Cardioprotective action of Nigella sativa seeds and honey mixture supplementation / Sarina Mohamad ... [et al.] - Mohamad, Sarina; Mohd Yusof, Hayati; Salim, Nor Jana; Omar, Ruzana (2013)
Hypercholesterolemia is one of the risk factors for cardiovascular disease (CVD). The effect of Nigella sativa (N. sativa) seeds or honey in modulating lipid profile has been widely studied. However, to date the study on its mixture is still limited to healthy adults. Therefore, this study was aimed to investigate the cardioprotective effects of N. sativa seeds and honey mixture on lipid profile modulation in healthy and also hypercholesterolemic subjects. Sixty-one subjects were assigned to control (n=20), healthy supplementation (n=20) and hypercholesterolemic supplementation (n=21) groups. Supplementation groups were administered with 50 mg/kg body weight the mixture daily for three months. The results demonstrated significant reductions in triglycerides (20.1%), ratio of TC:HDL-c (12.3%) and increased high density lipoprotein-cholesterol (15.3%), p 0.05 for healthy subjects. Moreover, supplementation significantly decreased the total cholesterol (6.2%), triglycerides (13.3%), ratio of TC:HDL-c (19.5%) and increased high density lipoprotein-cholesterol (21.0%), p 0.05 among hypercholesterolemic subjects. Based on the current findings, it seems that the mixture of N. sativa seeds and honey has beneficial therapeutic effects as cardioprotective supplement in dietary management of hypercholesterolemia.